2017
DOI: 10.15255/cabeq.2016.1031
|View full text |Cite
|
Sign up to set email alerts
|

Bioflocculation of Basic Dye onto Isolated Microbial Biopolymers

Abstract: Three purified biopolymers isolated from Bacillus velezensis (40B), Bacillus mojavensis (32A) and Pseudomonas (38A) strains were evaluated for dye decolourization as bioflocculants. The decolourization capacity of the three polymers was inspected using C.I 28 basic yellow dye as hazardous pollutant. The chemical compositions of these purified biopolymers were considered by HPLC and FTIR spectrum. The decolourization efficiency of the three purified biopolymers was determined using both real dye polluted wastew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Bacillus velezensis is known for its possession of azoreductases which are used to decolourise azo dyes of different molecular structures through enzymatic action 26,27 . It was also reported that B. velezensis contains a biopolymer that was isolated and used to decolourise azo dyes by bio-flocculation, with 91% efficiency 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Bacillus velezensis is known for its possession of azoreductases which are used to decolourise azo dyes of different molecular structures through enzymatic action 26,27 . It was also reported that B. velezensis contains a biopolymer that was isolated and used to decolourise azo dyes by bio-flocculation, with 91% efficiency 28 .…”
Section: Resultsmentioning
confidence: 99%